Mediação colaborativa: o diálogo entre o profissional da psicologia e o educador especial - Fontoura, Gabriele Marchionatti (2022)
This study is linked to the Graduate Program in Education (PPGE) of the Federal University of Santa Maria (UFSM), research line 3 (LP3) - Special Education, Inclusion and Difference. It aims to understand the interfaces of the Psychologist's and the Special Educator's actions in the school context to implement the inclusion of Special Education Target Public students. It is qualitative and exploratory research, with a case study. Two professionals participated in the research, a special educator and a psychologist, and both developed their functions in a school. The results analyzed qualitatively pointed to the lack of collaborative work in assisting students. The factors involved in this process involve the profile of communication between professionals, motivation, and school management. It is concluded that there are many challenges for collaborative mediation to occur, as they collide with different factors, such as work demands, the workload of professionals, and school organization/management, among others.